The sling and the blowgun as combat weapons in pre-Islamic Java; Notes on Old Javanese terms "gaṇḍi" and "tulup" - Jákl, Jiří (Wacana, Journal of the Humanities of Indonesia, 2017)
Two Old Javanese terms, ga i and tulup, are discussed in detail. While the term tulup appears to be unproblematic, ga i has previously been identified with a score of weapons, including bow, club, war hammer, and sling. I argue that the original meaning of this enigmatic term is 'projectile, pellet', while its second, derived meaning refers in most cases to 'sling', and, occasionally, to 'blowgun'. Both weapons are represented in the Old Javanese textual record as the weapons associated with predatory warfare, and with the forces of adharma. I have tentatively suggested that this configuration reflects the pre-modern reality of slingers and the men equipped with blowguns perceived as essentially foreign, non-Javanese elements, and hence possibly identified by pre-modern audiences with mercenaries sourced from Sumatra or other parts of Indonesia where the sling and blowgun were used regularly in warfare.